2018
DOI: 10.1186/s12884-018-1990-z
|View full text |Cite
|
Sign up to set email alerts
|

An account for barriers and strategies in fulfilling women’s right to quality maternal health care: a qualitative study from rural Tanzania

Abstract: BackgroundTanzania has ratified and abides to legal treaties indicating the obligation of the state to provide essential maternal health care as a basic human right. Nevertheless, the quality of maternal health care is disproportionately low. The current study sets to understand maternal health services’ delivery from the perspective of rural health workers’, and to understand barriers for and better strategies for realization of the right to quality maternal health care.MethodsSemi-structured in-depth intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…The findings of this study revealed that stigma was a major factor that prevented women from seeking timely obstetric fistula treatment. This was consistent with Khisa and Nyamongo [24, 25], who reported that women with fistula failed to reveal their condition because of stigma by community members. Women with fistula feared to lose their societal status in their community and found it difficult to speak about their problem for fear of the hatred they would receive.…”
Section: Discussionsupporting
confidence: 90%
“…The findings of this study revealed that stigma was a major factor that prevented women from seeking timely obstetric fistula treatment. This was consistent with Khisa and Nyamongo [24, 25], who reported that women with fistula failed to reveal their condition because of stigma by community members. Women with fistula feared to lose their societal status in their community and found it difficult to speak about their problem for fear of the hatred they would receive.…”
Section: Discussionsupporting
confidence: 90%
“…Similar Kenyan and Tanzanian studies found that providers' ability and willingness to provide RMC was strongly related to how they perceived their work environment including the availability of adequate staff and supplies, career opportunities, support services, and pay [34,35]. A recent global meta-review indicated that shortage of manpower and lack of drugs and equipment were major bottlenecks to improving the quality of maternal and newborn health care [36].…”
Section: Discussionmentioning
confidence: 95%
“…In a study of the barriers to quality maternal healthcare in Tanzania, authors discovered a lack of availability of adequate resources necessary to assist in a healthy delivery in health facilities. Such resources extended to human resources, as health facility workers were often over-worked resulting in disrespectful and/or abusive treatment for 19–28% of women seeking care at health facilities [20]. Given these conditions, it seems likely that women would be hesitant to disclose their pregnancy to someone they perceive as a part of this system.…”
Section: Discussionmentioning
confidence: 99%